Worlds of capitalism : institutions, governance and economic change in the era of globalization - Miller, Max H. (Routledge studies in governance and change in the global era., 2005)
This book draws together an international team of contributors, including Douglass North, Harold Demsetz and Michael Piore to assess the different types of capitalism that operate in the world today.